Eksplorasi Serat Nanas dengan Aplikasi Sulam Sashiko - Nabila Fasza (JURNAL RUPA, 2016)
Indonesia is a tropical country that has wide variety of flora and fauna. Various kind of plants are used for many needs. Fiber is an important crop that can be used by human after food crops. Beside the fruit is harvested for consumption, pineapple plant left a lot of leaf waste because after two to three harvest time, the old plant will be replace with new plants. This research aims to exploit pineapple fiber as an alternative raw material for textile by applying Sashiko embroidery on the exploration results of pineapple fiber. Design development is done with pineapple fibers exploration by using mango leaves as natural dye and Sashiko embroidery as their surface design. Sashiko embroidery created ornaments that can be used as an aesthetic element in the field of fabric. Sashiko embroidery application on the exploration of pineapple fiber is expected to raise the aesthetic value of order and pineapple fiber with a new structure that is intended for fesyen products.